The Role of Digital Marketing and Advertising in Honda Motorcycle Sales at PT. Indako Trading Coy during the Covid-19 Pandemic (Study Case Dealer in Medan, Binjai and Deli Serdang) - Santy Tan, Wandy Gozali (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
The covid-19 pandemic is a new disease since it entered Indonesia in April 2022. Of course, it becomes a problem for business actors where people are reluctant to consume. Digital marketing and advertising is the solution. Digital marketing and advertising are marketing strategies that are generally used to promote goods and services to customers. Thus, people will be more enthusiastic which ends in increasing sales. The population and sample in this study came from 30 dealers with a total of 36 people. The data analysis technique used multiple linear regression with F test criteria and t test. The results show that digital marketing has a negative effect on sales. This is based on the results of the t-count on the digital marketing variable of -1.733 with a significance level of 0.093. Advertising has positive effect on increasing sales. This is based on the results of the t-count on the promotion strategy variable of 3.362 with a significance level of 0.001. Then simultaneously digital marketing and advertising also have a significant effect on increasing sales of Honda motorcycles at PT. Indako Trading Coy. Based on the results of the study f-count 5.659 with a significance level less than 5%, namely 0.008.